Pengendalian Persediaan Sparepart Transmisi Bus dengan Analisis Always Better Control (ABC) dan Metode Economic Order Quantity (EOQ) di PT. Primajasa Perdanaraya Utama - Nuryana, Doni; Supriyono, Supriyono (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2025)
PT. Primajasa Perdanaraya Utama is a company engaged in the public transportation sector, offering various services such as intercity and interprovincial transport, inner-city routes, taxi services, tourism transport, and employee shuttles. In its operations, the company has been facing inventory management issues due to the absence of an effective policy in regulating stock levels and requirements. This has led to overstocking, which in turn increases the total inventory holding costs. To address this problem, the company implemented the ABC classification method to prioritize inventory items based on their significance, along with the Economic Order Quantity (EOQ) method to determine the most cost-efficient order quantity. The results from the EOQ analysis revealed that the total inventory cost for category A bus transmission spare parts could be reduced to IDR 48,634,982, resulting in savings of IDR 6,374,321 compared to the actual conditions. The implementation of this method achieved an efficiency improvement of 11.59%, demonstrating that this approach significantly contributes to reducing excess inventory and enhancing overall inventory management effectiveness.